FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN RODA KLOP OLEH TENAGA KESEHATAN DI WILAYAH KERJA PUSKESMAS LEPASAN - Yunita, Laurensia; Novita Dewi Iswandari (Midwifery And Complementary Care, 2023)
Background: The success of the family planning program in Indonesia is closely tied to the quality of counseling provided. Therefore, healthcare counselors must understand a client's medical condition and specific characteristics before contraceptive use. Healthcare providers have not yet utilized the KLOP Wheel as an aid in providing services before contraceptive use. The KLOP Wheel is important as it can reduce medical barriers and improve access to and quality of family planning services. This is especially relevant for clients with medical conditions or special characteristics, where certain contraceptive methods may worsen medical issues, pose additional health risks, or reduce contraceptive effectiveness. Objective: To determine the factors influencing the use of the KLOP Wheel as a medical eligibility screening tool by healthcare workers in the working area of Puskesmas Lepasan. Method: This research is a quantitative study using a descriptive method. The population consisted of 30 midwives working in the Puskesmas Lepasan area, selected using total sampling. Data analysis used the chi-square test with a questionnaire as the instrument. Results: The study found significant relationships between education level (ρ = 0.000), year of graduation (ρ = 0.000), length of work experience (ρ = 0.000), and knowledge (ρ = 0.000) with the use of the KLOP Wheel by healthcare workers. Conclusion: The ability and accuracy of healthcare providers in screening for medical eligibility criteria are expected to improve the quality of contraceptive services. However, the use of the KLOP Wheel has not yet been maximized. Its implementation also depends on the support and coordination efforts of the Ministry of Health and the National Population and Family Planning Board (BKKBN) to advance the family planning program. Keywords: medical eligibility criteria, knowledge, healthcare workers